PEMBERDAYAAN MASYARAKAT MELALUI EDUKASI ERGONOMI DAN SENAM PEREGANGAN UNTUK MENGURANGI RISIKO LOW BACK PAIN - Saumi Fijriyah; Berlina Putrianti; Murti Krismiyati; Amri Wulandari; Rahma Trisnaningsih; Budi Punjastuti (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2025)
Informal workers, such as farmers and artisans, face a high risk of Low Back Pain (LBP) due to non-ergonomic working postures. This community service project aimed to enhance workers' understanding and skills in preventing LBP through ergonomic education and stretching exercises. The methods included field observations, participatory education using visual media, and practical exercise training. The program involved 30 participants of productive age. Evaluation results showed a significant increase in knowledge, with the average score rising from 52.4 (Fair) to 88.7 (Good). Furthermore, 85% of participants successfully demonstrated the stretching movements independently. In conclusion, the combination of ergonomic education and stretching exercise training is effective in increasing preventive awareness of musculoskeletal disorders among informal workers. It is recommended that workers consistently implement five-minute stretching breaks every two hours to maintain productivity and spinal health.